Effectiveness of multi-disciplinary rehabilitation for patients with Neuromyelitis Optica. (3rd May 2016) - Nechemia, Yael; Moreh, Elior; Weingarden, Harold; Bloch, Ayala; Givon, Uri; Vaknin-Dembinsky, Adi; Schwartz, Isabella; Meiner, Zeev; Zeilig, Gabi
Abstract : Introduction : Neuromyelitis optica (NMO), previously considered a subtype of multiple sclerosis (MS), is now known to be a unique disorder associated with autoantibodies against aquaporin-4. The rehabilitation protocols for MS have been applied to NMO, without specific measures of efficacy. Purpose : The evaluation of the effectiveness of an MS type inpatient rehabilitation program for patients with NMO. Patient and Methods : Retrospective chart reviews of 15 inpatients with NMO and 32 inpatients with MS. Clinical severity was assessed by the Expanded Disability Status Scale (EDSS), functional assessments were scored using the Functional Independence Measure (FIM), the Montebello Rehabilitation Factor Score (MRFS), and the Functional Ambulation Category (FAC). There was a higher percentage of women in the NMO group (87% vs 56% P = 0.003). The MS group had significantly more cognitive and communication deficits (P = 0.003 and P = 0.00001). No significant differences were found in admission FIM, EDSS and FAC scores. Results : Both groups benefitted, however at discharge, the NMO group showed greater improvement in FIM scores (NMO admission 79 ± 24, discharge 98 ± 21; MS admission 80 ± 28, discharge 89 ± 28); and lower EDSS score (NMO from 7.2 ± 1.4 to 6.3 ± 1.4; MS from 7.4 ± 1.4 to 7 ± 1.5). Conclusions : Inpatient multidisciplinary rehabilitation programs available for the patients with MS may be successfully implemented for patients with NMO.